Characterization of physicochemical properties and sensory profile of red oncom in Dramaga District Bogor Regency - First Leisa Kurnia; Dase Hunaefi; Nancy Dewi Yuliana; Philipp Fuhrmann; Iryna Smetanska; Shin Yasuda (Hasanuddin University Food Science and Technology Study Program, 2023)
The production methods of red oncom can vary between different producers, leading to differences in sensory characteristics and compounds. This study aimed to characterize the physicochemical and sensory profile of red oncom that are most preferred by consumers. In this study, five samples of red oncom from Dramaga Districts, Bogor Regency, were selected as raw materials for physicochemical and sensory analysis. The proximate content of the five red oncom samples showed high levels of moisture, ash, and fat, but protein content in samples 259, 786, 615, and 478 was low. In contrast, the carbohydrate content in sample 615 was higher than proximate of red oncom by the Ministry of Health Republic Indonesia in 2019. The physical characteristics of color in some samples did not significantly differ in terms of L*, a*, C*, and h*values, although all samples exhibited a significant difference in terms of b* value. The texture characteristics of the five samples showed no significant differences in terms of springiness and cohesiveness, but significant variations were observed in hardness, gumminess, and chewiness. The sensory profiling involved 30 consumer panelists and 18 attributes, with sample 259 emerging as the most preferred among consumers. The analysis of consumption patterns based on five aspects of the food model, considering age and gender categories, revealed significant differences in several aspects, mainly related to food preferences (stir-fried, tutug rice, sauce, and fried oncom), self-conditions (feeling of sadness), and environmental conditions (hot weather). However, a significant difference was observed in the ecological aspect, specifically cold temperatures, when considering the gender category.